Does Higher Education Equalize Income Distribution? - Carnoy, Martin (International Higher Education, 2013)
Our recent research on higher educational change in the BRIC countries suggests that greatly expanding university enrollment has little positive effect on equalizing earnings distribution. The main reason is that the payoffs for graduates have continued to rise despite many more higher education graduates entering the labor market.